Utilization of Islamic Financial Instruments for Poverty Reduction and Sustainable Households in Nigeria - Amuda , Yusuff Jelili; Elshaarawy, Sanaa (Journal of Ecohumanism, 2024)
Predominant poverty has affected many households in Nigeria and little focus of attention is given to the utilization of Islamic financial instruments in addressing the challenges of poverty and sustainable household in the country. The study attempts to fill the gap in the existing literature concerning the utilization of Islamic financial instruments for poverty reduction and sustainable households in the country. Qualitative research method with an emphasis on critical content analysis was utilized. Materials or different sources were used whereby journals, online peer review, and library sources were considered for in-depth analysis of Islamic financial instruments for poverty reduction and sustainable households in attaining vision 2030 in the country. Adequate implementations of various Islamic financial instruments that would create room for inclusion through which low-income families or families in poverty would experience sustainable standard of living through an efficient Islamic financial instrument for their empowerment. Hence, it will expand the scope and understanding of Islamic financial instruments in the context of Nigeria. In so doing, there would be basis for restructuring the economic conditions of households experiencing an abject poverty by ensuring that their living conditions are improved for better. An emphasis on the judicious utilization of Islamic financial instruments especially towards sustainable households in the country is an integral part of expanding the understanding about the efficiency of Islamic financial instruments in the society. Central bank of Nigeria has issued a drafted framework for application of Islamic financial instruments and operation of Islamic banking system and less attention is given to the application of Islamic financial instruments in the country. This paper therefore has tried to provide explanation for the application of utilizing Islamic financial instruments for poverty reduction and sustainable households in the country.